Unpacking Mentorship in Mathematics Education: A Systematic Review - Constantino, Karl James P.; Lomibao, Laila S. (International Journal of Research in Interdisciplinary Studies, 2025)
This systematic literature review explores how mentorship, feedback, and standards-based professional development (PD) support the growth and instructional effectiveness of Highly Proficient Mathematics Teachers in the Philippines. Drawing on six Philippine-based peer-reviewed studies published between 2016 and 2025, the review identifies key practices and persistent gaps in mentoring frameworks aligned with the Philippine Professional Standards for Teachers (PPST) and the Results-Based Performance Management System (RPMS). Thematic synthesis reveals five major themes: mentoring practices and technical assistance, feedback-driven professional development, peer and collaborative learning, standards-based CPD, and the impact of mentorship on teacher competence and student outcomes. The findings highlight the importance of formative, dialogic feedback, structured mentoring protocols, and localized PD programs that reflect actual classroom needs. Despite consistent evidence of positive instructional outcomes, current mentoring systems remain underutilized, inconsistently implemented, and limited to public school contexts. This study emphasizes the need for a scalable, feedback-driven mentorship framework adaptable to both public and private school settings and tailored to the unique demands of mathematics education in the Philippines.